2017
DOI: 10.18632/oncotarget.19479
|View full text |Cite
|
Sign up to set email alerts
|

Effects of targeting SLC1A5 on inhibiting gastric cancer growth and tumor development in vitro and in vivo

Abstract: AimsTo investigate the oncogenic effects of SLC1A5 on gastric cancer development in vitro and in vivo.MethodsThe expression level of SLC1A5 was detected in 70 gastric cancer paraffin-embedded tissues by immunohistochemistry and also was detected in gastric cancer cell lines by qRT-PCR and western blotting analysis. The effects of knockdown SLC1A5 were analyzed on cell proliferation, cell cycle, the ability of cell migration and invasion and growth signaling pathway in vitro. By using subcutaneous xenograft mou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
30
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(33 citation statements)
references
References 27 publications
2
30
0
Order By: Relevance
“…Directly inhibiting transport of these nutrients may be a more efficacious approach to targeting the metabolic demands of PDAC and other cancers. Several reports have demonstrated that targeting glutamine transport through inhibition of SLC1A5/ ASCT2 has profound impacts on tumor growth in gastric and breast cancers (49,50). In addition, targeting other amino acid transporters, including SLC6A14 and SLC7A11/xCT, has also been reported to have significant impacts on tumor growth in PDAC (51,52).…”
Section: Discussionmentioning
confidence: 99%
“…Directly inhibiting transport of these nutrients may be a more efficacious approach to targeting the metabolic demands of PDAC and other cancers. Several reports have demonstrated that targeting glutamine transport through inhibition of SLC1A5/ ASCT2 has profound impacts on tumor growth in gastric and breast cancers (49,50). In addition, targeting other amino acid transporters, including SLC6A14 and SLC7A11/xCT, has also been reported to have significant impacts on tumor growth in PDAC (51,52).…”
Section: Discussionmentioning
confidence: 99%
“…Slc1A5 is a major transporter of glutamine in most cells. Knockdown of ASCT2 diminishes mTORC1 activity and tumor growth [124][125][126][127][128]. Although the absence of Slc1A5 did not significantly diminish intracellular Gln or Glu levels, it disrupted influx of leucine and diminished levels of other amino acids crucial for redox homeostasis [128].…”
Section: Glutamine Metabolismmentioning
confidence: 99%
“…There are few published studies reporting the association between ASCT2 and invasion and metastasis and the underlying mechanism remains elusive. Nevertheless, a higher expression of SLC1A5 in gastric cancer tissues has been correlated with clinicopathological features such as local invasion and lymph node metastasis [ 33 ]. Furthermore, SLC1A5 downregulation in vitro resulted in significant inhibition of gastric cells invasion and migration [ 33 ].…”
Section: Asct2 and Lat1: Their Contribution To The Hallmarks Of Camentioning
confidence: 99%
“…Although with fewer published studies, ASCT2 has been identified as a prognostic factor in hepatocellular [ 34 ], lung [ 35 ], colorectal [ 151 ], gastric [ 33 ], renal [ 28 ], ovarian [ 36 , 152 ], breast [ 153 ], tongue [ 140 ] and pancreatic cancer [ 76 ]. Furthermore, genetic variants in the SLC1A5 gene have also been implicated in hepatocellular carcinoma prognosis, with stage I patients carrying the rs2070246 TT genotype showing higher overall survival (OS) than carriers of CC genotype [ 154 ].…”
Section: Asct2 and Lat1: Their Clinical Significance In Cancermentioning
confidence: 99%